Ideological positioning of Extended Curriculum Programmes – a case study of a large South African research university - Ogude, N. A.; Rollnick, M. (South African Journal of Higher Education, 2022)
Extended Curriculum Programmes (ECPs) have been in existence in Africa and Southern Africa since the late 1970s. Various needs for programmes exist, but the primary motivator in the current South African context is a transformative one. While many historically white institutions have either scaled down or closed their ECPs, the University of Pretoria runs several large ECP programmes with the largest one located on the Mamelodi Campus. The location of the campus in a township offers many opportunities for transformative community engagement. This article interrogates the ideological underpinnings of the ECP programmes and other activities offered at the Mamelodi campus as these have evolved from their genesis in the University of Pretoria’s Foundation Year Programme in 2001. The article argues that a point has been reached where colour and ethnicity are no longer the only criteria for transformation, though the South African education system continues to be plagued by social inequality. Consequently, extended curriculum programmes need to serve the interests of the more disadvantaged section of the population, not the lower performing echelons of the more advantaged citizens, even though these may be black. The most recent government draft policy document provides possibilities for funding developmental interventions across the entire undergraduate education system but will require considerable sophistication in terms of pedagogy and curriculum design. The article concludes with a recommendation for a more responsive selection policy and curricula that provide a smoother transition into the programmes that students wish to access, including those with high barriers to entry.